We're all behavioral economists now. Issue 3 (3rd July 2019) - Angner, Erik
ABSTRACT: Behavioral economics has long defined itself in opposition to neoclassical economics, but recent developments suggest a synthesis may be on the horizon. In particular, several economists have argued that behavioral factors can be incorporated into standard theory, and that the days of behavioral economics are therefore numbered. This paper explores the proposed synthesis and argues that it is distinctly behavioral in nature – not neoclassical. Far from indicating that behavioral economics as a stand-alone research program is over, the proposed synthesis represents the consummate conversion of neoclassical economists into behavioral ones. GRAPHICAL ABSTRACT: